2022
DOI: 10.3389/fcell.2022.997838
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of fused-restrained Hedgehog signaling in chondrocytes is critical for epiphyseal growth plate maintenance and limb elongation in juvenile mice

Abstract: Hedgehog (Hh) signaling plays multiple critical roles in regulating chondrocyte proliferation and differentiation during epiphyseal cartilage development. However, it is still unclear whether Hh signaling in chondrocytes is required for growth plate maintenance during juvenile growth, and whether sustained activation of Hh signaling in chondrocytes promotes limb elongation. In this study, we first utilized Hh reporter mice to reveal that Hh signaling was activated in resting and columnar chondrocytes in growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The restraint of IHH activity level was critical for epiphyseal growth plate maintenance and limb elongation in mice. Chondrocyte-specific deletion of Smo or Sufu in growth plate chondrocytes to defects in epiphyseal growth plates and limb elongation (Xiu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The restraint of IHH activity level was critical for epiphyseal growth plate maintenance and limb elongation in mice. Chondrocyte-specific deletion of Smo or Sufu in growth plate chondrocytes to defects in epiphyseal growth plates and limb elongation (Xiu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the juvenile stage, TSC1 deletion in chondrogenic progenitors led to overactive mTORC1 activity and promoted stem-cell-like cells from the RZ generating more columnar chondrocytes (Newton et al, 2019 ). The IHH signals also regulate chondrocyte behavior, abnormal level of which leads to growth plate defect (Xiu et al, 2022 ). It is also interesting to know the effect of hyperactivation or inactivation of IHH in Gli1+ CPs, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the targeting efficiency and specificity of Krt19-CreER in the IVDs, Krt19-CreER mice were bred with R26-tdTomato reporter mice to produce Krt19-CreER ; R26-tdTomato mice. All above mice and their littermate controls were injected with tamoxifen at 2 weeks of age according to our previously described procedures [ 27 ]. To evaluate the effect of pharmacological inhibition of Hh signaling on the health of IVDs, ten 2-week-old C57BL/6 mice were randomly divided into two groups, and orally administered with either 50 mg/kg vismodegib (GDC) or vehicle solution (vehicle) as described previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, ablations of both Smo and SUFU decrease the growth, proliferation, differentiation, and survival of the cell. 36 In addition, OA is associated with abnormal Hh signaling or chondrocyte hypertrophy. 37 A previous study has shown that mechanical cues promote the Hh signaling and ADAMTS-5 expression in OA and exercise-induced muscle hypertrophy in satellite cells.…”
Section: Primary Cilium–mediated Mechanosensitive Signaling Pathwaymentioning
confidence: 99%